Unity in Diversity of Religions in Bumi Flobamora, Indonesia: From Traditional to Modern Pluralism - Jegalus, Norbertus; Atang, Ahmad; Binsasi, Norbertus Antoin (Millah: Journal of Religious Studies, 2024)
The religiously diverse society of NTT (Bumi Flobamora) has received national title as the most tolerant province in Indonesia. However, reality shows that there are religious conflicts, such as the rejection of the establishment of Islamic places of worship and the emergence of various forms of violence with religious nuances. This study attempts to provide a new contemporary social philosophy explanation for the development of religious social conditions. With the help of philosophical methods, the results show that the ideology of pluralism has long lived in Bumi Flobamora. However, this model of "traditional pluralism,” which is based on local wisdom and supported by the government's policy of harmony, is currently no longer in line with demands for universal human rights, because "traditional pluralism" shows the unequal treatment of people of different religions. Therefore, contemporary social philosophy develops a "modern pluralism,” which is built on the principle of equality. To strengthen this new model of pluralism, efforts are needed to overcome the weaknesses of communitarianism. The main weakness of communitarianism is that it opens up a space for religious appreciation that only emphasizes the togetherness and unity of a spiritual community and views those outside the community as other people who may or should even be excluded. The study concludes that the unity of religions in Bumi Flobamora will only survive if traditional pluralism is replaced with modern pluralism, which is in line with the Political Ethics of the Indonesian nation, Bhinneka Tunggal Ika, and the basic philosophy of Pancasila.